AICCRA Partners’ satisfaction survey results for 2024 - Giombini, Valentina; Calì, Davide; Schuetz, Tonya (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) supports climate-smart agriculture and climate information services through six country teams and thematic clusters. Its 2024 Partners’ Satisfaction and Partnership Efficacy survey collected 417 responses from 227 stakeholders across 12 clusters, achieving a 70% response rate. AICCRA uses this feedback to strengthen partnerships, improve service delivery, and inform performance metrics such as Intermediary Progress Indicator on ‘Use or adaptation of AICCRA-funded climate relevant knowledge products, decision-making tools and services confirmed by surveyed partners and stakeholders. The survey assessed 46 AICCRA services, reporting an average usage rate of 84% and a satisfaction score of 88%. Services were perceived as demand-driven by 67% of respondents. Capacity strengthening (43% of services) reached over 70,000 people, while tools and technologies (35%) reached nearly 9,000. Technical assistance (22%) scored highest in satisfaction (90%). The survey also indicated improved integration of climate-smart Gender and Social Inclusion (GSI) (87%). The multilingual survey supports citizen engagement and captures diverse perspectives across Africa's climate resilience landscape.